Application of flywheel energy storage for heavy haul locomotives - Spiryagin, M.; Wolfs, Peter; Szanto, F.; Sun, Y.; Cole, C.; Nielsen, D. (Elsevier, 2015)
© 2015 Elsevier Ltd. At the present time, trains in heavy haul operations are typically hauled by several diesel-electric locomotives coupled in a multiple unit. This paper studies the case of a typical consist of three Co-Co diesel-electric locomotives, and considers replacing one unit with an alternative version, with the same design parameters, except that the diesel-electric plant is replaced with flywheel energy storage equipment. The intelligent traction and energy control system installed in this unit is integrated into the multiple-unit control to allow redistribution of the power between all units. In order to verify the proposed design, a three-stage investigation has been performed as described in this paper. The initial stage studies a possible configuration of the flywheel energy storage system by detailed modelling of the proposed intelligent traction and energy control system. The second stage includes the investigation and estimation of possible energy flows using a longitudinal train dynamics simulation. The final stage compares the conventional and the proposed locomotive configurations considering two parameters: fuel efficiency and emissions reduction.